MENACING MEMES? AFFECT AND EFFECTS OF POLITICAL INTERNET MEMES - Huntington, Heidi (AoIR Selected Papers of Internet Research, 2015)
Scholarship demonstrates that internet memes – digital-media based, intertextual, participatory creations – are polyvocal, political discourse (Milner, 2012) and grassroots action and advocacy (Shifman, 2014). In democratic and nondemocratic societies, citizens use memes to react, critique, protest, and speak truth to power. In a late November 2014 post for The Spectator, a long-running conservative British magazine, Isabel Hardman lamented the spread of a particular meme, the purpose of which was ostensibly to critique the British Parliament by highlighting MPs’ lack of concern for social issues, in contrast to their over concern for their own benefits. In the post, headlined “The Menace of Memes,” Hardman traced the origins of photos used in the meme to argue that the memes were “deceitfully spreading lies” through a combination of out-of-context images and over-simplification of Parliament’s processes (Hardman, 2014). Underlying Hardman’s essay was the assumption that these memes contributed to viewers’ understanding of the issue. While an interesting assumption, it is also an understudied one. Though the influence of media on politics has long been of interest to scholars, this research has been largely focused on traditional forms of media. With the rise of social media has come a blurred distinction regarding what counts as “media.” When nearly anyone can write a blog post or share a meme, it becomes necessary to understand how user-generated media influences politics. While this work has begun with studies of relationships between social media use and information-seeking or traditional political participation, there is more work yet to be done to understand how user-generated content, like internet memes, influence those who view them as media. By exploring this question of meme effects, this paper seeks to answer Shifman’s (2014) call for future meme research to establish what constitutes an effect of memes and how such effects might be measured.